Economic assessment of renewable power generation based on wind speed and solar radiation in urban regions - Y. Kassem; H. Gökçekuş; H. Çamur (Global Journal of Environmental Science and Management)
Economic evaluation of 12 MW grid-connected wind farms and PV power plants in two regions in Northern Cyprus for electricity generation was investigated. The wind speed, sunshine duration, and solar global radiation characteristics were analyzed using monthly data collected over 17 years (2000-2016) for Girne and nine years (2008-2016) for Lefkoşa, which were measured at various heights. The result showed that during 2000-2016, the mean wind speed at Girne was 2.505 m/s and during 2008-2016, the mean wind speed at Lefkoşa was 2.536 m/s. The result showed that both regions had annual mean wind speed greater than 2 m/s at 10 m height. Moreover, the annual mean sunshine duration and global solar radiation were higher than seven h/day and 15 MJ./m2/day at a height of 2 m for all studied regions, respectively. In this study, eight distribution functions were used to analyze the wind speeds and global solar radiation data in each region. The results indicated that Weibull and Logistic were the best distributions for analyzing the wind speeds and global solar radiation data of the studied regions, respectively. Furthermore, the capacity factors of the selected regions ranged between 1.92% and 48.53%. Based on the renewable energy cost results, it is found that the generation costs of the wind farm were between 0.023 and 0.04 Euro/kWh, while the PV plant was between 0.08 and 0.098 Euro/kWh.